Germline genome-wide association studies in women receiving neoadjuvant chemotherapy with or without bevacizumab. Issue 6 (June 2018) - Ingle, James N.; Kalari, Krishna R.; Wickerham, Donald Lawrence; von Minckwitz, Gunter; Fasching, Peter A.; Furukawa, Yoichi; Mushiroda, Taisei; Goetz, Matthew P.; Barman, Poulami; Carlson, Erin E.; Rastogi, Priya; Costantino, Joseph P.; et al.
Abstract : Neoadjuvant chemotherapy (NAC) for breast cancer is widely utilized, and we performed genome-wide association studies (GWAS) to determine whether germ-line genetic variability was associated with benefit in terms of pathological complete response (pCR), disease-free survival, and overall survival in patients entered on the NSABP B-40 NAC trial, wherein patients were randomized to receive, or not, bevacizumab in addition to chemotherapy. Patient DNA samples were genotyped with the Illumina OmniExpress BeadChip. Replication was attempted with genotyping data from 1398 HER2-negative patients entered on the GeparQuinto NAC study in which patients were also randomized to receive, or not, bevacizumab in addition to chemotherapy. A total of 920 women from B-40 were analyzed, and 237 patients achieved a pCR. GWAS with three phenotypes (pCR, disease-free survival, overall survival) revealed no single nucleotide polymorphisms (SNPs) that were genome-wide significant (i.e. P ⩽5E−08) signals; P values for top SNPs were 2.04E−07, 5.61E−08, and 5.63E−08, respectively, and these SNPs were not significant in the GeparQuinto data. An ad-hoc GWAS was performed in the patients randomized to bevacizumab (457 patients with 128 pCR) who showed signals on chromosome 6, located within a gene, CDKAL1, that approached, but did not reach, genome-wide significance (top SNP rs7453577, P =2.97E−07). However, this finding was significant when tested in the GeparQuinto data set ( P =0.04). In conclusion, we identified no SNPs significantly associated with NAC. The observation, in a hypothesis-generating GWAS, of an SNP in CDKAL1 associated with pCR in the bevacizumab arm of both B-40 and GeparQuinto requires further validation and study. Abstract : Supplemental Digital Content is available in the text.